Drum Communication Program Intervention in Older Adults With Cognitive Impairment and Dementia at Nursing Home: Preliminary Evidence From Pilot Randomized Controlled Trial - Miyazaki, Atsuko; Okuyama, Takashi; Mori, Hayato; Sato, Kazuhisa; Ichiki, Masahiko; Nouchi, Rui (Frontiers in Aging Neuroscience, 2020)
Introduction: Inactivity and consequent deterioration of cognitive and physical function is a major concern among older adults with the limited walking ability and need a high level of care in nursing homes. We aimed to test whether a drumming communication program (DCP) that uses the rhythmic response function of the elderly with cognitive impairment, dementia, and other debilitating disorders would improve their cognitive and physical function. Methods: We conducted a Randomized Controlled Trial (RCT) to investigate the effects of the DCP in 46 nursing home residents who needed high levels of nursing care. The participants were randomly assigned to an intervention and control group. The intervention group attended 30 min of the DCP thrice a week for 3 months. Cognitive function was measured using the Mini-Mental State Examination-Japanese (MMSE-J) and Frontal Assessment Battery (FAB). Physical function was measured using grip strength and active upper limb range of motion with the dominant hand. Body composition was measured using bioelectrical impedance analysis (BIA). These measures were analyzed before and after the DCP intervention period, and data for the two groups were compared thereafter. Results: Initially, the participants had low scores on the MMSE-J, and 84.78% of them used wheelchairs. Following the DCP intervention, the MMSE-J and FAB scores of the DCP group improved significantly. In terms of motor function, the active range of motion of the wrist palmar and the shoulder flexion improved in the intervention group. Regarding body composition, the skeletal muscle mass index, total body protein, and the dominant hand muscle mass that was adding physical load decreased. Conclusions: The DCP provided the participants with an opportunity to engage in continued exercise for 3 months. The intervention group exhibited improved cognitive function and upper limb motion range, and changes in body composition. The results suggest that DCP can be used as an intervention method to promote exercise and improve various health and cognitive functions. Trial Registration: This trial was registered at the University Hospital Medical Information Network Clinical Trial Registry (UMIN000024714) on 4 November 2016. The URL is available at https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000028399.